Estudio De Los Proyectos De Residencia Profesional Como Generadores De Productividad Y Cambio Organizacional - Gómez-Márquez, Montserrat; Quintero-Fuentes, Martha Patrícia; López-Trejo, Homero Janai; LLanillo-Navales, Jesús Gerardo; Marín-Ramos, Martha; Méndez-Cervantes, Juan Manuel; Eurrieta-Ortiz, María Isela; García-Arroyo, Luz del Carmen; Romo-Celis, Fernando Agustín; Carrera-Salazar, Claudia Olivia; Palomares, Luís Antônio Calderón; González-Pérez, Manuel (European Scientific Journal, ESJ, 2018)
Professional residency projects (PRP) have the theoretical knowledge and skills of the professional discipline of the students who develop them. Each professional residency project provides companies with viable opportunities and solutions that contribute to productivity. We sought to identify the influence between the application of the PRP and the changes in effectiveness and efficiency. This application affects the internal control and generates an organizational change. This paper analyzed some effects of the PRP through a descriptive and documentary study. The data collection instrument was validated through the Pearson correlation. The dependence between PRPs and the generation of productivity, change in internal control was calculated. The results obtained were generated with the chi-square statistical independence test. This test showed four variables that are more dependent on each other. The theoretical square chi of a pair of variables was graphed and the theoretical inverse function: p-value vs. square chi of 1 degree of freedom to observe the intersection. In conclusion, it was observed that the projects of professional residency influence in the internal control and the productivity of the companies via efficacy-efficiency.